Shi’a Community in Malang City as a Subaltern: Strategy to Celebrate Religious Freedom Amidst Sunni Domination - Johan Wahyudi (Journal of Governance, 2022)
Everyone has the right to practice their religion and adhere to their beliefs. Unfortunately, minority sects such as the Shi’a community cannot celebrate their beliefs freely as citizens. They had to hide their identity as Shi’a congregations in order to prevent conflicts and to protect themselves and their families. Against this background, this article aims to examine the strategy of the Shi’a community in Malang City in exercising freedom of religion and belief as a minority religious group in the midst of the Sunni community. This study puts the Shi’a religious group in Malang City as a subaltern that is often discriminated against and excluded socially and politically. This study's data was gathered through interviews and a review of the literature. The selection of research informants was carried out through a purposive sampling technique. By using a qualitative approach with the case study method, this study finds at least three strategies developed by the Shi’a community in Malang City to practice their freedom of religion and belief, namely the Taqiyyah strategy, strengthening the congregation through Huseiniyah recitation, and teaching their children about two different versions of prayer.